2012
DOI: 10.1021/nl3002205
|View full text |Cite
|
Sign up to set email alerts
|

Electron Tunneling through Ultrathin Boron Nitride Crystalline Barriers

Abstract: We investigate the electronic properties of heterostructures based on ultrathin hexagonal boron nitride (h-BN) crystalline layers sandwiched between two layers of graphene as well as other conducting materials (graphite, gold). The tunnel conductance depends exponentially on the number of h-BN atomic layers, down to a monolayer thickness. Exponential behaviour of I-V characteristics for graphene/BN/graphene and graphite/BN/graphite devices is determined mainly by the changes in the density of states with bias … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

52
738
1
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 788 publications
(813 citation statements)
references
References 20 publications
52
738
1
3
Order By: Relevance
“…~4 K). This fitting result is quite consistent with the raw R-T curve, which shows a dramatic increase of R j below 4 K. At low temperatures (T < 4 K), the tunneling current is determined by the density of states (DOS) in the graphene (D G ) and in the Bi 2 Se 3 (D TI ), which can be expressed as 11,12,17,32 where T(E) is the tunneling probability and the function ( ) is the Fermi-Dirac distribution function. In the low temperature region, the integral energy can be restricted to the range between and + eV, where is the chemical potential.…”
supporting
confidence: 83%
“…~4 K). This fitting result is quite consistent with the raw R-T curve, which shows a dramatic increase of R j below 4 K. At low temperatures (T < 4 K), the tunneling current is determined by the density of states (DOS) in the graphene (D G ) and in the Bi 2 Se 3 (D TI ), which can be expressed as 11,12,17,32 where T(E) is the tunneling probability and the function ( ) is the Fermi-Dirac distribution function. In the low temperature region, the integral energy can be restricted to the range between and + eV, where is the chemical potential.…”
supporting
confidence: 83%
“…5 and the vs. n dependence of hBN using graphite and gold electrodes [24]. These data indicate that the R c value is largely determined by the interlayer hBN thickness.…”
Section: Andmentioning
confidence: 72%
“…The EBD obtained in this study is in agreement with that reported previously for thin BN. 15 It is interesting that EBD for BN decreases with increasing the thickness. The similar behavior is also observed for SiO2.…”
mentioning
confidence: 99%
“…10 Therefore, BN is considered to be an ideal insulator for layered channel materials. Several studies of the optical, 11 mechanical, 12 phonon, 13 electrical tunneling, 14,15 oxidation resistance, 16 and hydrophobic 17 properties of BN have also been reported.…”
mentioning
confidence: 99%